Early life exposure of infants to benzylpenicillin and gentamicin is associated with a persistent amplification of the gut resistome - Dhrati V. Patangia; Ghjuvan Grimaud; Carol-Anne O’Shea; C. A. Ryan; Eugene Dempsey; Catherine Stanton; R. Paul Ross (Microbiome, 2024)
Abstract Background Infant gut microbiota is highly malleable, but the long-term longitudinal impact of antibiotic exposure in early life, together with the mode of delivery on infant gut microbiota and resistome, is not extensively studied. Methods Two hundred and eight samples from 45 infants collected from birth until 2 years of age over five time points (week 1, 4, 8, 24, year 2) were analysed. Based on shotgun metagenomics, the gut microbial composition and resistome profile were compared in the early life of infants divided into three groups: vaginal delivery/no-antibiotic in the first 4 days of life, C-section/no-antibiotic in the first 4 days of life, and C-section/antibiotic exposed in first 4 days of life. Gentamycin and benzylpenicillin were the most commonly administered antibiotics during this cohort’s first week of life. Results Newborn gut microbial composition differed in all three groups, with higher diversity and stable composition seen at 2 years of age, compared to week 1. An increase in microbial diversity from week 1 to week 4 only in the C-section/antibiotic-exposed group reflects the effect of antibiotic use in the first 4 days of life, with a gradual increase thereafter. Overall, a relative abundance of Actinobacteria and Bacteroides was significantly higher in vaginal delivery/no-antibiotic while Proteobacteria was higher in C-section/antibiotic-exposed infants. Strains from species belonging to Bifidobacterium and Bacteroidetes were generally persistent colonisers, with Bifidobacterium breve and Bifidobacterium bifidum species being the major persistent colonisers in all three groups. Bacteroides persistence was dominant in the vaginal delivery/no-antibiotic group, with species Bacteroides ovatus and Phocaeicola vulgatus found to be persistent colonisers in the no-antibiotic groups. Most strains carrying antibiotic-resistance genes belonged to phyla Proteobacteria and Firmicutes, with the C-section/antibiotic-exposed group presenting a higher frequency of antibiotic-resistance genes (ARGs). Conclusion These data show that antibiotic exposure has an immediate and persistent effect on the gut microbiome in early life. As such, the two antibiotics used in the study selected for strains (mainly Proteobacteria) which were multiple drug-resistant (MDR), presumably a reflection of their evolutionary lineage of historical exposures—leading to what can be an extensive and diverse resistome. Video Abstract